(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Negotiation and implementation of business transaction agreements are crucial for enhancing financial performance and sustainability of firms in Uganda. Business transactions, whether public procurement contracts, private-sector collaborations, or investment agreements, require careful negotiation to optimize resource allocation, reduce risk, and maximize returns. This review examines the processes, challenges, and outcomes of business negotiations in Uganda using a financial management lens. It emphasizes how budgeting, cash flow management, cost-benefit analysis, risk assessment, and performance monitoring influence both negotiation strategies and contract implementation. Drawing from financial management theories, transaction cost economics, and negotiation scholarship, the review highlights gaps in financial literacy, institutional enforcement, and professional negotiation capacity among Ugandan firms and SMEs. Case studies from agriculture, oil and gas, and public procurement illustrate common negotiation pitfalls, including misaligned financial expectations, weak due diligence, and lack of monitoring mechanisms. The review concludes that integrating financial management principles into negotiation and contract execution strengthens compliance, reduces disputes, enhances profitability, and fosters sustainable business relationships.